Group-assisted purification (GAP) chemistry for the synthesis of Velcade via asymmetric borylation of N-phosphinylimines - Xie, Jian-bo; Luo, Jian; Winn, Timothy R.; Cordes, David B.; Li, Guigen (Beilstein Journal of Organic Chemistry, 2014)
A new approach to the anticancer drug Velcade was developed by performing asymmetric borylation of an imine anchored with a chiral N-phosphinyl auxiliary. Throughout the 7-step synthesis, especially in the imine’s synthesis and in the asymmetric borylation reactions, operations and work-up were conducted in simple and easy ways without any column chromatographic purification, which defines the GAP (group-assisted purification) chemistry concept. It was found that the optically pure isomer (dr > 99:1) can be readily obtained by washing the crude mixture of the asymmetric borylation reaction with hexane; the chiral N-phosphinyl auxiliary can be easily recovered after deprotection is finished. Several other N-phosphinylimines were also investigated for the asymmetric borylation reaction. The absolute configuration of the borylation product was confirmed by single crystal X-ray diffraction analysis.
Keywords: asymmetric borylation; GAP chemistry; organophosphorous; N-phosphinylimine; Velcade